2006
DOI: 10.1136/sti.2006.021535
|View full text |Cite
|
Sign up to set email alerts
|

Why are children still being infected with HIV? Experiences in the prevention of mother-to-child transmission of HIV in south London

Abstract: The overall transmission rate of 2% attests to the efforts of the multidisciplinary care team in managing this population which is often hard to reach. Clearly, good systems are needed to trace those women who default. Further data are needed regarding in utero transmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When women return, staff members must be available to meet them. Training for program staff may be necessary in interaction skills, for instance, Thailand reported success in PMTCT services by providing training and retraining for staff on a periodic basis; enhancing counseling skills of staff; encouraging open communication and clear delineation of tasks and responsibilities [56]. A related study in Ukraine also found similar findings [57].…”
Section: Discussionmentioning
confidence: 85%
“…When women return, staff members must be available to meet them. Training for program staff may be necessary in interaction skills, for instance, Thailand reported success in PMTCT services by providing training and retraining for staff on a periodic basis; enhancing counseling skills of staff; encouraging open communication and clear delineation of tasks and responsibilities [56]. A related study in Ukraine also found similar findings [57].…”
Section: Discussionmentioning
confidence: 85%
“…In a UK study, the rate of MTCT of HIV was 2% [18], comparable to less than 2% reported from clinical trials in other developed countries [19]. The UK study further noted that 70.6% of their subjects received HAART consisting of 3 or more drugs [18]. …”
Section: Discussionmentioning
confidence: 89%
“…In economically-developed countries, perinatal transmission of HIV has been reduced to 1% as a result of the use of Pediatric AIDS Clinical Trials Group study (PACTG 076) regimen, highly active anti-retroviral therapy (HAART), appropriate management of labor and delivery; and avoidance of breastfeeding [17]. In a UK study, the rate of MTCT of HIV was 2% [18], comparable to less than 2% reported from clinical trials in other developed countries [19]. The UK study further noted that 70.6% of their subjects received HAART consisting of 3 or more drugs [18].…”
Section: Discussionmentioning
confidence: 99%
“…Following HIV acquisition, HIV antibody tests may remain negative for 4–5 weeks 57 . Evidence is accumulating reporting infant perinatal infection arising from maternal HIV infection acquired during pregnancy or the postpartum period 58–60 . As some pregnant women are at increased risk of acquiring HIV during pregnancy as a consequence of concurrent sexually transmitted infections (STIs), intravenous drug abuse, or multiple partners, 61 enhanced HIV testing strategies should be considered, especially in parts of the world where HIV is common 3–5 .…”
Section: Repeat Hiv Testing Is Important To Detect Hiv Infection Acqumentioning
confidence: 99%